2009
DOI: 10.1016/j.jtcvs.2008.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Vagal nerve stimulation prevents reperfusion injury through inhibition of opening of mitochondrial permeability transition pore independent of the bradycardiac effect

Abstract: Vagal stimulation would be a potential adjuvant therapy for the rescue of ischemic myocardium from reperfusion injury, and the protective effects are independent of its bradycardiac effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
78
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 28 publications
8
78
3
Order By: Relevance
“…42,43 Moreover, the concentration of by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from acetylcholine for therapy in the pathological conditions is usually higher than the physiological level. 40,44 In the present study, treatment with acetylcholine (10…”
Section: Discussionmentioning
confidence: 79%
“…42,43 Moreover, the concentration of by guest on May 11, 2018 http://atvb.ahajournals.org/ Downloaded from acetylcholine for therapy in the pathological conditions is usually higher than the physiological level. 40,44 In the present study, treatment with acetylcholine (10…”
Section: Discussionmentioning
confidence: 79%
“…The results of the present study demonstrated that VS was capable of decreasing myocardial enzyme expression levels and cardiomyocyte apoptosis, which is an important mechanism of cell death. Furthermore, previous studies (16)(17)(18) have demonstrated that VS or the neurotransmitter ACh may exert cardioprotective effects through the regulation of mitochondrial biogenesis and function. The prolonged opening of the mitochondrial permeability transition pore induces cell death through the rapid depletion of ATP and activation of death messengers, such as caspases, which have a key role in apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In conscious animal with healed myocardial infarction, direct vagal stimulation also effectively prevents ventricular arrhythmias including ventricular fibrillation [13,44]. Multiple mechanisms are shown to involve in the anti-arrhythmic effect of VNS, such as bradycardiac effect [42], anti-adrenergic effects [4], prevention of the loss of phosphorylated connexin 43 proteins [45], and inhibition of the opening of the mitochondrial permeability transition pore [46]. Although the cardiac protective effect of VNS is mainly mediated by muscarinic receptor, recent study indicated that the vagal antifibrillatory action can be mediated by neuronal nitric oxide released by intracardiac neurons or nerve fibers [47], which reduces the maximal slope of the ventricular action potential restitution curves [48].…”
Section: Es-pns and Vasmentioning
confidence: 99%